PENGARUH PROFITABILITAS DAN ECO-EFFICIENCY TERHADAP NILAI PERUSAHAAN DENGAN CEO POWER SEBAGAI VARIABEL MODERASI - Astuti, Narulita Widhi; Handayani, Mega (E-Jurnal Akuntansi TSM, 2025)
This study aims to determine the effect of profitability as measured by return on assets (ROA) and return on equity (ROE) and eco-efficiency on firm value, with CEO power as a moderating variable. This study uses secondary data taken from the financial statements and annual reports of companies engaged in the construction and building subsector listed on the Indonesia Stock Exchange during the period 2022-2024. The sample selection was carried out using a purposive sampling method, sample 22 companies with 5 of which were outliers, so the total number of companies included in the final sample was 17. For data analysis, techniques used included multiple linear regression analysis, t-tests, and moderated regression analysis (MRA), which were processed using IBM SPSS software. 25. The findings of this study show that the results of the partially t-tests indicate that ROA has a positive impact on firm value, while ROE and eco-efficiency show no effect on firm value. In the partially MRA analysis, CEO power was shown to moderate the influence of ROA and ROE on firm value, but did not have the ability to moderate the influence of eco-efficiency on firm value.